2020
DOI: 10.1177/1747493020967256
|View full text |Cite
|
Sign up to set email alerts
|

Encephaloduroarteriosynangiosis (EDAS) revascularization for symptomatic intracranial atherosclerotic steno-occlusive (ERSIAS) Phase-II objective performance criterion trial

Abstract: Background Intracranial atherosclerotic disease (ICAD) is one of the most challenging stroke etiologies, with frequent recurrences despite optimized medical management. Encephaloduroarteriosynangiosis (EDAS) is an indirect revascularization method that produces extra-cranial collaterals to intracranial vessels. We present the results of a phase-II trial of EDAS in intracranial atherosclerotic disease patients. Aims To evaluate the feasibility, safety, and preliminary efficacy of EDAS in intracranial atheroscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…Based on our experience, we believe there are 3 main factors that mitigate the risk of perioperative stroke in patients with ICAD undergoing EDAS: standardized hemodynamic and ventilatory parameters that are strictly controlled during the anesthetic period, consistent and rigorous IMM in the perioperative period, and decreased risk of surgical complications, given the simplicity of the EDAS procedure compared with direct bypass. This hypothesis is further supported by the recent ERSIAS PC trial that showed a 7.7% risk of perioperative stroke after EDAS in patients with ICAD, 7 a more favorable rate than those demonstrated in EC-IC (12%) 22 and COSS 23 (15%) direct bypass trials.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Based on our experience, we believe there are 3 main factors that mitigate the risk of perioperative stroke in patients with ICAD undergoing EDAS: standardized hemodynamic and ventilatory parameters that are strictly controlled during the anesthetic period, consistent and rigorous IMM in the perioperative period, and decreased risk of surgical complications, given the simplicity of the EDAS procedure compared with direct bypass. This hypothesis is further supported by the recent ERSIAS PC trial that showed a 7.7% risk of perioperative stroke after EDAS in patients with ICAD, 7 a more favorable rate than those demonstrated in EC-IC (12%) 22 and COSS 23 (15%) direct bypass trials.…”
Section: Discussionmentioning
confidence: 65%
“…Although the EDAS technique has been described several times in the literature, no reports have evaluated the multidisciplinary approach to improve operative outcomes and the effects of maintaining strict medical management in patients at high risk of recurrent stroke. As the role of EDAS potentially expands to treat conditions such as ICAD, 3,5,7,21 it is necessary to identify the detailed nuances and variables that can be controlled to ensure good outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of the still ongoing Chinese Middle Cerebral Artery Occlusion Surgery Study [23] are expected to provide further insights into the role of bypass surgery for steno-occlusive disease. Furthermore, the recently published American Encephaloduroarteriosynangiosis Revascularization for Symptomatic Intracranial Arterial Stenosis phase II trial provided the evidence of safety and strong signals of efficacy of indirect bypass in addition to the best medical management [24], supporting advancement to a consecutive phase IIb/III trial.…”
Section: Discussionmentioning
confidence: 99%
“…6,15 However, for steno-occlusive disease, recent evidence has raised the possibility that indirect bypass may provide good protection against future stroke. 16,17 Over time, it is likely that at least for STA-middle cerebral artery bypass for moyamoya disease, a standard benchmark for perioperative complications may be established similar to that for carotid endarterectomy or carotid stenting. In this context, it is essential that the right patients are selected for surgery, and the right procedures are offered.…”
mentioning
confidence: 99%